The Utilization of Digital Communication Media Genre Radio in Successful BKKBN Programs - yasha langitta setiawan; Puryanto Puryanto; Januardi Nasir (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
The development of communication technologies has changed people's lives who are now more likely to use Internet-based or digital communication media. BKKBN West Sumatra is a government agency which innovates by using digital media called